The Availability and Distribution of Dentists in Rural ZIP - Katherine K. Knapp, PhD; Kevin Hardwick, DDS, MPH (Blackwell Synergy, 2000)
This paper maps dentists, primary care physicians, physician assistants, nurse practitioners, and nurse midwives in rural areas and rural areas meeting criteria as undersewed for primary health care